2002
DOI: 10.1016/s0738-3991(01)00195-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting adherence to prophylactic medication in adolescents with asthma: an application of the ASE-model

Abstract: An explanatory framework, referred to as the attitude/social influence/self-efficacy-model (ASE-model), was utilised to explain future self-reported adherence of adolescents to daily inhaled prophylactic asthma medication. The objective was to investigate the long-term influence of these earlier reported cognitive variables and other psychological and medical determinants on self-reported adherence 1 year later. Data were collected, via a questionnaire, from 86 adolescents with asthma (aged 11 through 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
3
39
1
Order By: Relevance
“…However, improved self-management of asthma relies upon several behavioral factors (e.g., daily symptom monitoring, treatment adherence) that may be influenced by asthma self-efficacy (ASE) [1,4], which reflects a patient's confidence in their ability to carry out the necessary selfmanagement behaviors required to control asthma symptoms and prevent exacerbations [5]. Although previous studies have linked higher general self-efficacy to improved asthma self-management behaviors, including more regular use of peak-flow meters, better medication adherence, and fewer hospitalizations for asthma [6,7], we are aware of no studies to date that have assessed the association between asthma-specific self-efficacy and levels of asthma control. Moreover, we are aware of only two studies to date to assess the impact of self-efficacy on asthma-related quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, improved self-management of asthma relies upon several behavioral factors (e.g., daily symptom monitoring, treatment adherence) that may be influenced by asthma self-efficacy (ASE) [1,4], which reflects a patient's confidence in their ability to carry out the necessary selfmanagement behaviors required to control asthma symptoms and prevent exacerbations [5]. Although previous studies have linked higher general self-efficacy to improved asthma self-management behaviors, including more regular use of peak-flow meters, better medication adherence, and fewer hospitalizations for asthma [6,7], we are aware of no studies to date that have assessed the association between asthma-specific self-efficacy and levels of asthma control. Moreover, we are aware of only two studies to date to assess the impact of self-efficacy on asthma-related quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported self-efficacy as an important predictor of PAM adherence in patients with asthma, 7,21,23,26,[29][30][31] others have attached less or no influence to this factor. 14,15,32 With regard to social influence, previous research has stressed the role of social support in therapy adherence in chronic diseases in general; 33,34 however, this is not yet clear with regard adherence to PAM.…”
mentioning
confidence: 99%
“…Deenen 26 found that adult patients with the opinion that important others (partner, children, doctor, friends, family, and colleagues) expect them to follow the prescribed PAM (ie, social norm) are more likely to adhere. According to Van Es et al, 30 however, patients are less likely to adhere if they perceive a strong normative influence of their doctor to follow the PAM prescriptions. This was only the case if previous behavior (the extent to which the patient already used PAM the year before the measurement) was included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that patients' views should be taken into account during medical decision-making, particularly in diseases such as asthma [4]. In addition, patients' beliefs about their illness play a key role in determining their adherence to treatment [5], which is an important aspect of self-management [6].…”
Section: Introductionmentioning
confidence: 99%